Effectiveness of classroom seating arrangement on students’ reading achievement - Tee, Xue Ting (2019)
This research examined the effectiveness of row, cluster, and horseshoe seating arrangements on students’ reading achievement in an English class. Date were gathered from a sample of 24 Form Two students in a public secondary school located in Kampar, Perak. Through pre- and post-tests, students answered ten multiple-choice and comprehension questions regarding the reading passages they read. The questions followed a general pattern to test students’ lower-, middle- and higher-order thinking skills. Following that, a focus group interview was conducted among five selected participants, each after intervening a new seating arrangement which lasted approximately two weeks. Throughout the interviews conducted, they were asked to share their feeling and experience upon seating a new arrangement. Results showed that seating in clusters led to the highest improvement in students’ reading performance with an average reading score of 8.29%, as compared to seating in rows and horseshoe. This concludes that teachers should attempt different types of classroom seating arrangements, in order to find out what best suits the students’ needs and creates an environment in which they can maximize students’ reading performance. Suggestions are made for future researchers to examine underlying factors that might influence the empirical results of this study.